Iron limitation in the marine cyanobacterium Trichodesmium reveals new insights into regulation of photosynthesis and nitrogen fixation - Küpper, Hendrik; Šetlík, Ivan; Seibert, Sven; Prášil, Ondrej; Šetlikova, Eva; Strittmatter, Martina; Levitan, Orly; Lohscheider, Jens; Adamska, Iwona; Berman-Frank, Ilana (The New phytologist, 2008)
* As iron (Fe) deficiency is a main limiting factor of ocean productivity, its effects were investigated on interactions between photosynthesis and nitrogen fixation in the marine nonheterocystous diazotrophic cyanobacterium Trichodesmium IMS101. * Biophysical methods such as fluorescence kinetic microscopy, fast repetition rate (FRR) fluorimetry, and in vivo and in vitro spectroscopy of pigment composition were used, and nitrogenase activity and the abundance of key proteins were measured. * Fe limitation caused a fast down-regulation of nitrogenase activity and protein levels. By contrast, the abundance of Fe-requiring photosystem I (PSI) components remained constant. Total levels of phycobiliproteins remained unchanged according to single-cell in vivo spectra. However, the regular 16-kDa phycoerythrin band decreased and finally disappeared 16-20 d after initiation of Fe limitation, concomitant with the accumulation of a 20-kDa protein cross-reacting with the phycoerythrin antibody. Concurrently, nitrogenase expression and activity increased. Fe limitation dampened the daily cycle of photosystem II (PSII) activity characteristic of diazotrophic Trichodesmium cells. Further, it increased the number and prolonged the time period of occurrence of cells with elevated basic fluorescence (F(0)). Additionally, it increased the effective cross-section of PSII, probably as a result of enhanced coupling of phycobilisomes to PSII, and led to up-regulation of the Fe stress protein IsiA. * Trichodesmium survives short-term Fe limitation by selectively down-regulating nitrogen fixation while maintaining but re-arranging the photosynthetic apparatus.
Keywords: Photosynthesis; železo; Chlorophyll; Carotenoids; Microscopy, Fluorescence; Photosystem II Protein Complex; Iron; Nitrogen Fixation; fotosystém I (proteinový komplex); Down-Regulation; fluorescenční mikroskopie; Blotting, Western; chlorofyl; karotenoidy; proliferace buněk; down regulace; Culture Media; Phycoerythrin; kultivační média; sinice; fotosystém II (proteinový komplex); Kinetics; fykoerythrin; fykobiliproteiny; kinetika; Photosystem I Protein Complex; nitrogenasa; Cell Proliferation; Phycobiliproteins; Cyanobacteria; western blotting; fotosyntéza; Nitrogenase; fixace dusíku